Genkwanin: An emerging natural compound with multifaceted pharmacological effects - El Menyiy, Naoual; Aboulaghras, Sara; Bakrim, Saad; Moubachir, Rania; Taha, Douae; Khalid, Asaad; Abdalla, Ashraf N.; Algarni, Alanood S.; Hermansyah, Andi; Long, Chiau Ming *; Rusu, Marius Emil; Bouyahya, Abdelhakim (Elsevier, 2023)
Plant bioactive molecules could play key preventive and therapeutic roles in chronological aging and the pathogenesis of many chronic diseases, often accompanied by increased oxidative stress and low-grade inflammation. Dietary antioxidants, including genkwanin, could decrease oxidative stress and the expression of pro-inflammatory cytokines or pathways. The present study is the first comprehensive review of genkwanin, a methoxyflavone found in several plant species. Indeed, natural sources, and pharmacokinetics of genkwanin, the biological properties were discussed and highlighted in detail. This review analyzed and considered all original studies related to identification, isolation, quantification, investigation of the biological and pharmacological properties of genkwanin. We consulted all published papers in peer-reviewed journals in the English language from the inception of each database to 12 May 2023. Different phytochemical demonstrated that genkwanin is a non-glycosylated flavone found and isolated from several medicinal plants such as Genkwa Flos, Rosmarinus officinalis, Salvia officinalis, and Leonurus sibiricus. In vitro and in vivo biological and pharmacological investigations showed that Genkwanin exhibits remarkable antioxidant and anti-inflammatory activities, genkwanin, via activation of glucokinase, has shown antihyperglycemic activity with a potential role against metabolic syndrome and diabetes. Additionally, it revealed cardioprotective and neuroprotective properties, thus reducing the risk of cardiovascular diseases and assisting against neurodegenerative diseases. Furthermore, genkwanin showed other biological properties like antitumor capability, antibacterial, antiviral, and dermato-protective effects. The involved mechanisms include sub-cellular, cellular and molecular actions at different levels such as inducing apoptosis and inhibiting the growth and proliferation of cancer cells. Despite the findings from preclinical studies that have demonstrated the effects of genkwanin and its diverse mechanisms of action, additional research is required to comprehensively explore its therapeutic potential. Primarily, extensive studies should be carried out to enhance our understanding of the molecule's pharmacodynamic actions and pharmacokinetic pathways. Moreover, toxicological and clinical investigations should be undertaken to assess the safety and clinical efficacy of genkwanin. These forthcoming studies are of utmost importance in fully unlocking the potential of this molecule in the realm of therapeutic applications.